2014
DOI: 10.3748/wjg.v20.i17.4934
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D improves inflammatory bowel disease outcomes: Basic science and clinical review

Abstract: Vitamin D deficiency is commonly diagnosed among patients with inflammatory bowel disease (IBD). Patients with IBD are at risk of low bone density and increased fractures due to low vitamin D levels, long standing disease, and frequent steroid exposures; as a result, it is well established that vitamin D supplementation in this population is important. There is increasing support for the role of vitamin D in strengthening the innate immune system by acting as an immunomodulator and reducing inflammation in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 74 publications
1
72
1
5
Order By: Relevance
“…Vitamin D can be acquired either by endogenous production or through consumption of foods containing vitamin D. Vitamin D is produced when the skin comes in contact with ultraviolet light, and can also be found in egg yolks, as well as certain seafood and dairy products . Some foods such as orange juice may be supplemented with Vitamin D which is absorbed in the small intestine . The vitamin D that is produced or absorbed is metabolised in the liver to produce 25‐hydroxyvitamin D (25‐OH vitamin D), which is activated by the kidney to form 1,25 dihydroxyvitamin D. The primary circulating form of vitamin D is 25‐OH vitamin D, which is often measured clinically to determine vitamin D sufficiency …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D can be acquired either by endogenous production or through consumption of foods containing vitamin D. Vitamin D is produced when the skin comes in contact with ultraviolet light, and can also be found in egg yolks, as well as certain seafood and dairy products . Some foods such as orange juice may be supplemented with Vitamin D which is absorbed in the small intestine . The vitamin D that is produced or absorbed is metabolised in the liver to produce 25‐hydroxyvitamin D (25‐OH vitamin D), which is activated by the kidney to form 1,25 dihydroxyvitamin D. The primary circulating form of vitamin D is 25‐OH vitamin D, which is often measured clinically to determine vitamin D sufficiency …”
Section: Discussionmentioning
confidence: 99%
“…While there are insufficient data regarding treatment of IBD with vitamin D, studies have shown that patients who are vitamin D deficient are also likely to have complications of IBD including increased risk of hospitalisation, stricturing disease, surgical resection, pancolitis in UC and use of steroids earlier after diagnosis. 8,9 In addition, higher vitamin D levels have been associated with a higher quality of life among patients with IBD, as measured by the short IBD questionnaire. 10 Compared to placebo, treatment with vitamin D was associated with decreased risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical studies and basic research support a role of intestine VDR signaling in the pathogenesis and treatment of inflammatory bowel diseases [116]. Vitamin D deficiency was associated with higher risk of inflammatory bowel diseases, while higher vitamin D intake lowers this risk.…”
Section: Activation Of Nuclear Receptors By Bile Acidsmentioning
confidence: 99%
“…11,12 Vitamin D supplementation has been reported to have clinical benefit in reducing IBD occurrence and relapse and in improving outcomes. 12 VDR regulates the expression of cathelicidin antimicrobial peptides (CAMPs), β-defensins, and autophagy regulator ATG16L1 [13][14][15] and therefore possesses some antibiotic properties. For example, [1,25(OH) 2 D 3 ] leads to up-regulation of CAMPs and the killing of intracellular Mycobacterium tuberculosis in human monocytes.…”
Section: Introductionmentioning
confidence: 99%